Superolateral Dislocation in a Pediatric Hip Associated with Labrum Entrapment and Overgrowth of the Ischial Part of the Acetabulum - Karakurt, Lokman; Belhan, Oktay (Fırat University, 2006)
We describe a child who had old unreduced traumatic hip dislocation associated with overgrowth of the ischial part of the acetabulum and interposition of the labrum. Open reduction was performed, and overgrowth part of the ischium and interposed labrum were excised for obtaining a concentric reduction of the hip joint. At the three-year follow-up visit, result was excellent. ©2006, Fırat Üniversitesi, Tıp Fakültesi

Travmatik kalça çıkığı gelişen bir çocuk olguda, tam redüksiyonu engelleyen oluşumlar olarak labrum interpozisyonu ve asetabulumun iskial parçasının aşırı büyümesi saptandı. Olguya açık redüksiyon yapıldı, interpoze labrum parçası eksize edildi ve aşırı büyümüş olan asetabulumun iskial kısmı inceltildi. Ameliyat sonrası 3. yıldaki kontrolde redüksiyon tamdı ve fonksiyonel sonuç mükemmeldi. ©2006, Fırat Üniversitesi, Tıp Fakültesi
Çocuk Süperolateral Kalça Çıkığı ile Beraber Labrum İnterpozisyonu ve Asetabulumun İskial Parçasının Aşırı Büyümesi: Olgu Sunumu